Isolation of Tetrahymena pyriformis From Several Infected Pet Fish Species And a Regime For Its Treatment - Ahmed Al- Tayyar, Omar Bassim (The Iraqi Journal of Veterinary Medicine, 2005)
Tetrahymena pyriformis has been firstly isolated from brood Goldfish(Carassius auratus) Common, Fantail, Ryukin, Veiltail and Moor, Black molly(Poecilia sphenops), Gourami (Trichogaster trichopterus), red Swordtail(Xiphophorus helleri), Guppy (Poecilia reticulata), deep Angelfish(Pterophyllum scalare) and brood Algae eater (Hypostomus plecostomus) inIraq. The infected fish suffered from mucus hypersecretion large hyperemicareas on the skin, and slight shedding of the scales. The incidence percentage ofinfection was 100 %. Rising water temperature was up to 29 – 30cْ for one timeand methylene blue was at a concentration of 5 ppm for 24 hours. Sodiumchloride at a concentration of 2 % for one minute and two minutes has noobvious effect on Tetrahymena pyriformis. Treatment with NaCl at theconcentration of 1% for 20 minutes for three consecutive days achieved the bestresults.